A new weighted injury severity scoring system: Better predictive power for pediatric trauma mortality. Issue 2 (August 2018) - Shi, Junxin; Shen, Jiabin; Caupp, Sarah; Wang, Angela; Nuss, Kathryn E.; Kenney, Brian; Wheeler, Krista K.; Lu, Bo; Xiang, Henry
Abstract : BACKGROUND: An accurate injury severity measurement is essential for the evaluation of pediatric trauma care and outcome research. The traditional Injury Severity Score (ISS) does not consider the differential risks of the Abbreviated Injury Scale (AIS) from different body regions nor is it pediatric specific. The objective of this study was to develop a weighted ISS (wISS) system for pediatric blunt trauma patients with better predictive power than ISS. METHODS: Based on the association between mortality and AIS from each of the six ISS body regions, we generated different weights for the component AIS scores used in the calculation of ISS. The weights and wISS were generated using the National Trauma Data Bank. The Nationwide Emergency Department Sample (NEDS) was used to validate our main results. Pediatric blunt trauma patients younger than 16 years were included, and mortality was the outcome. Discrimination (areas under the receiver operating characteristic curve, sensitivity, specificity, positive predictive value, negative predictive value, concordance) and calibration (Hosmer-Lemeshow statistic) were compared between the wISS and ISS. RESULTS: The areas under the receiver operating characteristic curves from the wISS and ISS are 0.88 versus 0.86 in ISS of 1 to 74 and 0.77 versus 0.64 in ISS of 25 to 74 ( p < 0.0001). The wISS showed higher specificity, positive predictive value, negative predictive value, and concordance when they were compared at similar levels of sensitivity. The wISS had better calibration (smaller Hosmer-Lemeshow statistic) than the ISS (11.6 vs. 19.7 for ISS = 1–74 and 10.9 vs. 12.6 for ISS = 25–74). The wISS showed even better discrimination with the Nationwide Emergency Department Sample. CONCLUSION: By weighting the AIS from different body regions, the wISS had significantly better predictive power for mortality than the ISS, especially in critically injured children. LEVEL OF EVIDENCE AND STUDY TYPE: Prognostic/epidemiological, level IV. Abstract : Supplemental digital content is available in the text.